Structuring times and activities in the oncology visit. (May 2019) - Sterponi, Laura; Zucchermaglio, Cristina; Fatigante, Marilena; Alby, Francesca
Abstract: In this paper we examine how doctor and patient coordinate actions in interaction towards the smooth accomplishment of the medical visit. Such coordination entails primarily the management of time and praxis, i.e. the apportionment of time to the tasks to be completed during the visit; and it is not an easy enterprise, for a number of reasons: 1) the tasks to be carried out during the visit are not familiar in equal measure to doctor and patient; 2) the extent of attention to be devoted to each task cannot be fully determined in advance but requires ongoing judgment and calibration; 3) generally, the timeframe of the visit is relatively limited. Our ethnographic and conversation analytic study of oncological visits shows that doctor and patient rely on a range of semiotic resources to achieve mutual understanding and coordinated actions. In particular, our analysis has identified textual artifacts and metapragmatic utterances as key semiotic components in the coordination and negotiation of the temporal trajectories and courses of actions that constitute and traverse the oncology visit. Highlights: The structuring of time and activity in oncology visits was studied. Ethnographic observation and conversation analysis of videorecordings were carried out. The structuring of time and activity is a joint accomplishment by doctor and patient. Textual artifacts and metapragmatic utterances are the key semiotic resources used. Effective management of visits' timing may be more beneficial than having more time.